The Quest-(ion) for Diversity. (January 2019) - Ali, Amir
This article attempts to look at the quest for diversity by posing a question about how effective the concept has been in securing meaningful diversity in the public sphere of liberal polities. It distinguishes between diversity and difference to suggest that difference poses a greater challenge to liberal polities as compared to diversity. It then goes onto look at diversity in relation to democracy, especially in the context of a worsening climate of democracy across the world. The article suggests that the prospects for diversity are unlikely to be bright either in the contemporary conjuncture or the immediate future. The article ends by suggesting that diversity is caught between the forces of globalization and the insular nationalism that has welled up from the hinterlands of nation-states.